Heinäntorjuntaan soveltuvia katteita testattu - Poteri, Marja (Metsäntutkimuslaitos, 2002)
Selostus artikkelista: Siipilehto Jouni. 2001. Effect of weed control with fibre mulches and herbisides on the initial development of spruce, birch and aspen seedlings on abondened farmland. Silva Fennica 35(4): 403-414.
Julkaisusatoa